A Note on Operator Sampling and Fractional Fourier Transform. (11th September 2011) - Zhang, Qingyue
Abstract : This paper presents that the kernel of the fractional Fourier transform (FRFT) satisfies the operator version of Kramer's Lemma (Hong and Pfander, 2010), which gives a new applicability of Kramer's Lemma. Moreover, we give a new sampling formulae for reconstructing the operators which are bandlimited in the FRFT sense.